Character’s visual image creation in multimedia projects - Khynevych, Ruslana; Batrak, Vadym; Skliarenko, Valerii; Vasylenko, Oleksandra (Art and Design, 2025)
In the modern information society, character design plays a key role in shaping visual culture and effective communication in the media space. Characters become conductors of meaning, brand symbols, narrative elements that influence the emotional perception of the audience. The relevance of this study was driven by the rapid development of digital technologies, the integration of visual content into various fields (from education to advertising), and the growing role of characters in digital communications, where not only aesthetics but also the psychological persuasiveness of the image is significant. The purpose of the present study was to consider character design as a crucial element of multimedia projects, analyse animation works, and identify key stages that influence the formation of a visual image. The study employed an integrated approach that and developing character design in animated films, video games, and other multimedia products. The artistic, technical, and conceptual solutions employed by designers were analysed, and the criteria for an effective visual image, such as recognisability, emotional expressiveness, adaptability, and stylistic relevance to the context were identified. Particular attention was paid to the influence of cultural, social, and psychological factors on the formation of characters and their role in the narrative structure of the artistic work. Based on the analysis of seven popular characters of different eras, styles, and formats, the study generalised the key features of successful design. It was found that the combination of simplicity of form, cultural symbolism, and design flexibility ensures an emotional connection with the udience and effective communication in the media. The findings of this study can be used in the practice of character design for animation, games, cinema, and interactive media.